Implementasi Organizational Citizenship Behaviour dan Kelelahan Emosional: Analisis Servant leadership dan Self Efficacy Karyawan - Chintya Ones Charli; Rahmi (Psyche 165 Journal, 2023)
In a job, there must be a lot of challenges faced by employees, both physically, emotionally, and other problems. This study aims to analyze the role of emotional exhaustion on Organizational Citizenship Behavior with leadership and self-efficacy as independent variables. The population in this study are private employees in the city of Padang. To determine the sample used the Maximum Likelihood Estimation which requires a sample size of 100-200 samples, the researcher will take a sample of 100-200 employees who work in private companies in the city of Padang. The technique used in this research is a survey method in the form of a questionnaire with a sample of private employees working in the city of Padang. The research design uses associative and data analysis techniques used are path analysis using the smartPLS application with regard to the results of the outer model and inner model. The results of this study indicate that there is no significant effect of the variable of Leadership on Emotional Exhaustion for employees who work in the city of Padang, then there is a significant effect of the variable of self-efficacy on Emotional Exhaustion for employees working in the city of Padang, then there is a significant effect of Leadership on Organizational Citizenship Behavior on employees who work in the city of Padang, then there is a significant influence of self-efficacy on Organizational Citizenship Behavior for employees who work in the city of Padang. There is no significant influence of leadership on Organizational Citizenship Behavior through emotional exhaustion. There is a significant effect of Self Efficacy on Organizational Citizenship Behavior through emotional exhaustion. This research model uses 4 (four) variables and applies the intervening concept.